A study of habit of fast food eating among school going adolescents and parental advice and its relation with their nutritional status - Singh, Mukesh Vir; Singh, D. K.; Yadav, R. K.; Shukla, K. M.; Sharma, I. K.; Prajapati, N. C. (International Journal of Research in Medical Sciences, 2017)
Background:A study of habit of fast food eating among school going adolescents and parental advice and its relation with their nutritional status. Methods: Design: an epidemiological analytic observational study. Subjects: 600 adolescents’ 15-19 years of age, studying in 11 and 12 classes and included both boys and girls. A single observer interviewed each student and gathered the information regarding their eating habits. It was recorded on a pre-tested open and closed ended Performa. Nutritional status was assessed by BMI. The adolescents for the purpose of analysis were broadly grouped in two groups. Group I (those having normal BMI ranging 18.5 to 25) and group II (Malnourished i.e. those having BMI <18.5 to >25). Group II adolescents were further divided into group IIa (Underweight, BMI<18.5) and group IIb is (Over weight and obese BMI >25). Results:Adolescents who took both fast food and soft drinks 73.1% were malnourished (group II) as compared to those who did not take both the things 13.7% in group II. Difference was found to be statistically significant (p value <0.01). Out of 73.1% who took both fast food and soft drinks 62.1% and 11.0% were in group IIa (Underweight, BMI <18.5) and group IIb (Over weight and obese BMI >25) subsequently. Incidence of malnutrition was significantly less in 12.4% adolescents’ interfered by their parents as compared to 69.6% of those where parents was not interfering. Difference was found to be statistically significant (P value <0.01). Conclusion: A habit of fast food eating and taking soft drink provokes malnutrition. Interference in eating by parents is beneficial among adolescents.